Aqueous zinc ion battery electrolyte, preparation method thereof and long cycle life application

CN122931087APending Publication Date: 2026-10-16FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610920699.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为解决现有技术中水系锌离子电池锌负极枝晶生长、析氢腐蚀严重、循环寿命短的技术问题,本申请提供一种水系锌离子电池电解液及其制备方法和应用

Benefits of technology

“去离子水”,是指通过离子交换、反渗透、电渗析或蒸馏等工艺去除水中绝大部分阴阳离子杂质(如钙、镁、钠、铁、铜、氯、硫酸根等离子)所得到的高纯度水。为避免杂质离子对电池电化学性能的干扰(如导致副反应、降低库仑效率、诱发枝晶生长等),本申请中所述去离子水的电阻率通常不低于18.25 MΩ·cm(25°C下)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an aqueous zinc ion battery electrolyte and a preparation method and application thereof. The electrolyte comprises an amphiphilic zwitterionic additive, a zinc salt and water; the amphiphilic zwitterionic additive comprises a hydrophobic long-chain alkyl and a hydrophilic phosphorylcholine head group. The amphiphilic zwitterionic additive can self-assemble on the surface of a zinc negative electrode to form a dense and ordered hydrophobic interface protection layer, meanwhile, the phosphate anion regulates the solvation structure of zinc ions, and the quaternary ammonium cation provides an electrostatic shielding effect, and the triple synergistic mechanism effectively inhibits zinc negative electrode dendrite growth, hydrogen evolution reaction and corrosion side reaction, and significantly improves the cycle life and coulombic efficiency of the aqueous zinc ion battery. The electrolyte preparation method is simple, only needs to be stirred and dissolved at room temperature, is low in cost, and is suitable for large-scale application. The aqueous zinc ion battery adopting the electrolyte has excellent long cycle stability, and provides an effective technical approach for the practical application of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to an aqueous zinc-ion battery electrolyte and its preparation method, as well as its long cycle life application, belonging to the field of electrochemical energy storage technology. Background Technology

[0002] With the large-scale development of renewable energy, the demand for energy storage technologies with large capacity, low cost, and high safety is becoming increasingly urgent. Aqueous zinc-ion batteries (AZIBs) use metallic zinc (Zn) as the negative electrode active material and aqueous solution as the electrolyte solvent. They have advantages such as abundant raw material reserves, low cost, safety and non-toxicity, and environmental friendliness, and are considered one of the most promising next-generation large-scale energy storage technologies.

[0003] However, aqueous zinc-ion batteries face severe technical challenges in practical applications. During charge-discharge cycles, the zinc anode exhibits the following main problems: (1) Dendrite growth: Zn 2+ Uneven deposition on the negative electrode surface leads to the formation of needle-like or dendritic zinc dendrites. The dendrites penetrate the separator, causing an internal short circuit and resulting in battery failure. (2) Hydrogen evolution reaction (HER): Water molecules in the aqueous electrolyte undergo reduction decomposition on the zinc negative electrode surface, producing hydrogen gas, which not only consumes active zinc and electrolyte, but also leads to an increase in battery internal pressure. (3) Corrosion: The zinc negative electrode comes into direct contact with the aqueous electrolyte, resulting in a self-corrosion reaction. Insulating byproducts (such as Zn(OH)2, ZnSO4·Zn(OH)2·nH2O, etc.) are generated on the negative electrode surface, increasing the interfacial impedance and reducing the coulombic efficiency (CE). The above problems are superimposed on each other, which seriously restricts the cycle life and practical application of aqueous zinc-ion batteries.

[0004] Existing improvement strategies mainly include: using high-concentration electrolytes (such as lithium acetate, potassium bis(fluorosulfonyl)imide, etc., ≥10 mol / kg) to reduce free water activity through solvation; using small organic molecule additives (such as sulfonyl lactones, formic acid, shikimic acid, etc.) to regulate interfacial chemistry; and using short-chain phosphocholine additives to suppress dendrite formation and hydrogen evolution through electrostatic shielding and solvation regulation. However, among the above schemes, high-concentration electrolytes are costly and complex to prepare; short-chain phosphocholine (alkyl chains containing only 2 carbons) does not have significant amphiphilicity and cannot form a dense and ordered hydrophobic interfacial protective layer on the zinc anode surface, resulting in limited interfacial protection and requiring further improvement in battery cycle life.

[0005] Therefore, developing a novel electrolyte additive that can construct a stable and dense interfacial protective layer on the surface of the zinc anode while achieving multiple synergistic protections is of great significance for achieving long cycle life of aqueous zinc-ion batteries. Summary of the Invention

[0006] To address the technical problems of dendrite growth, severe hydrogen evolution corrosion, and short cycle life of zinc anodes in existing aqueous zinc-ion batteries, this application provides an aqueous zinc-ion battery electrolyte, its preparation method, and its application.

[0007] According to one aspect of this application, an aqueous zinc-ion battery electrolyte is provided, the aqueous zinc-ion battery electrolyte comprising an amphiphilic zwitterionic additive, a zinc salt and water; the amphiphilic zwitterionic additive comprising a hydrophobic group and a hydrophilic zwitterionic head group; the hydrophobic group is selected from long-chain alkyl groups; the hydrophilic zwitterionic head group is selected from phosphocholine groups.

[0008] Studies have shown that long-chain alkyl groups (such as dodecyl groups) endow amphiphilic zwitterionic additives with significant amphiphilicity, enabling them to undergo directional self-assembly on the zinc anode surface to form a dense and ordered hydrophobic interfacial protective layer. The hydrophobic effect of long-chain alkyl groups drives the additive molecules to oriented on the zinc anode surface, effectively preventing direct contact between water molecules and corrosive anions and the zinc anode.

[0009] Preferably, the long-chain alkyl group is a dodecyl group; Preferably, the amphiphilic zwitterionic additive is n-dodecyl phosphate choline (DPC). Alternatively, the structural formula of n-dodecylphosphocholine is as follows:

[0010] n-Dodecylphosphocholine (DPC) is an amphoteric compound. Its long C12 hydrophobic alkyl chain endows the molecule with significant amphiphilicity, enabling it to undergo directional self-assembly on the zinc anode surface to form a dense and ordered hydrophobic interface protective layer.

[0011] Optionally, the concentration of the amphiphilic zwitterionic additive is 0.005 mol / L to 1 mol / L.

[0012] Optionally, the concentration of the amphiphilic zwitterionic additive is selected from any value or a range of any two of 0.005 mol / L, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.5 mol / L, and 1 mol / L.

[0013] Optionally, the concentration of the amphiphilic zwitterionic additive is selected from any value or a range of any two of 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, and 0.5 mol / L.

[0014] Optionally, the zinc salt is selected from at least one of zinc sulfate (ZnSO4) and zinc trifluoromethanesulfonate (Zn(CF3SO3)2).

[0015] Optionally, the concentration of the zinc salt is 0.5 mol / L to 4 mol / L.

[0016] Optionally, the concentration of the zinc salt is selected from any value or a range of any two of 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, and 4 mol / L.

[0017] Optionally, the water is deionized water.

[0018] In this application, the amphiphilic zwitterionic additive plays a triple synergistic protective role in aqueous zinc-ion battery electrolytes: (1) Hydrophobic interface layer protection: The hydrophobic effect of long-chain alkyl groups drives the additive molecules to self-assemble in a directional manner on the zinc anode surface, forming a dense and ordered hydrophobic protective layer, which effectively blocks the direct contact between water molecules and corrosive anions and the zinc anode, and inhibits hydrogen evolution reaction (HER) and corrosion side reactions. (2) Solution structure regulation: The phosphate anion (—OPO3H-) in the phosphate choline head group reacts with Zn 2+ Coordination occurs, entering Zn 2+ The solvation shell replaces some water molecules, reducing Zn2. + The proportion of free water molecules in the solvation layer is optimized for Zn. 2+ Solvation structure promotes Zn 2+ Uniform deposition / dissolution; (3) An electrostatic shielding effect is generated on the zinc atoms already deposited on the surface, making subsequent Zn 2+ Preferential deposition in flat regions rather than dendrite tips suppresses disordered dendrite growth. This triple mechanism works synergistically to significantly improve the cycle life and coulombic efficiency (CE) of aqueous zinc-ion batteries.

[0019] This application uses long-chain alkyl groups (preferably C). 12 This endows the additive molecules with amphiphilicity, enabling them to not only possess electrostatic shielding and solvation regulation functions, but also to form a dense, ordered hydrophobic interface protective layer on the zinc anode surface.

[0020] According to another aspect of this application, a method for preparing an aqueous zinc-ion battery electrolyte as described above is provided, comprising the following steps: adding zinc salt to water and stirring to dissolve it, then adding an amphiphilic zwitterionic additive, and continuing to stir until completely dissolved to obtain the aqueous zinc-ion battery electrolyte.

[0021] Optionally, the stirring time is 10 min to 60 min.

[0022] Optionally, the stirring time is selected from any value of 10 min, 15 min, 20 min, 30 min, 45 min, 60 min, or a range of any two.

[0023] Optionally, the stirring is carried out at room temperature (20~25°C) without the need for heating or special atmosphere protection.

[0024] According to another aspect of this application, an aqueous zinc-ion battery is provided, comprising a positive electrode, a negative electrode, a separator, and an aqueous zinc-ion battery electrolyte as described above.

[0025] Optionally, the negative electrode is metallic zinc or a zinc alloy.

[0026] Preferably, the negative electrode is a zinc sheet or zinc foil with a purity of not less than 99.9%.

[0027] Optionally, the purity of the negative electrode is selected from any value of 99.9%, 99.95%, 99.99%, or a range of any combination of both.

[0028] Optionally, the active material of the positive electrode is selected from ammonium vanadate (NH4V4O). 10 Vanadium pentoxide (V2O5) or vanadium dioxide (VO2).

[0029] In this application, "amphiphilic zwitterionic additive" refers to a compound that contains both hydrophobic groups (such as alkyl chains, aromatic rings, or cholesterol skeletons) and hydrophilic zwitterionic groups in the same molecule. The hydrophobic groups impart affinity between the molecule and the electrode interface or hydrophobic environment, while the hydrophilic zwitterionic groups impart good solubility and ion conductivity in aqueous electrolytes. The amphiphilic zwitterionic additive can regulate interfacial properties by forming an ordered arrangement at the electrode / electrolyte interface through its amphiphilic characteristics. A zwitterion is an ionic compound that contains both independent positively charged and negatively charged groups within the same molecule, resulting in an overall electrically neutral molecule. The positively and negatively charged groups are covalently bonded to different positions on the same molecular skeleton. Unlike ordinary salts (which consist of independent cations and anions bonded by ionic bonds), zwitterions have their positive and negative charge centers fixed within the same molecule by covalent bonds. The "phosphocholine group" is a zwitterionic head group formed by the covalent linkage of a phosphate anion and a quaternary ammonium cation through an ethoxylated linker (—OCH2CH2—). In this group, the phosphate portion carries a negative charge, and the quaternary ammonium portion carries a positive charge, resulting in overall electroneutrality and good water solubility and biocompatibility. The phosphocholine group is a major hydrophilic head group in natural phospholipid molecules and a core structural unit of the phospholipid bilayer in cell membranes. "Deionized water" refers to high-purity water obtained by removing most of the anions and cations (such as calcium, magnesium, sodium, iron, copper, chloride, sulfate, etc.) from water through processes such as ion exchange, reverse osmosis, electrodialysis, or distillation. To avoid interference from impurity ions on the electrochemical performance of the battery (such as causing side reactions, reducing coulombic efficiency, inducing dendrite growth, etc.), the resistivity of the deionized water described in this application is generally not less than 18.25 MΩ·cm (at 25°C).

[0030] The beneficial effects that this application can produce include: 1) This application uses an amphiphilic zwitterionic additive, whose long-chain alkyl group endows the molecule with amphiphilicity and self-assembly ability, which can form a dense and ordered hydrophobic interface protective layer on the zinc anode surface. This protective effect is not possessed by existing short-chain phosphocholine additives; 2) The additive in this application comprehensively inhibits dendrite growth, hydrogen evolution reaction, and corrosion side reactions of the zinc anode through a triple synergistic mechanism of hydrophobic interface layer protection, solvation structure regulation, and electrostatic shielding, and has a better comprehensive protective effect than existing single or dual mechanism additives; 3) The electrolyte preparation method of this application is simple, requiring only room temperature stirring and dissolution, without complex processes, and is low in cost, making it suitable for large-scale applications; 4) Aqueous zinc-ion batteries using the electrolyte of this application exhibit significantly improved cycle life and coulombic efficiency (CE), and demonstrate excellent long-term cycle stability. For example, in a Zn||VO2 full cell system, tested at a current density of 0.2 A / g, after 3600 cycles (7000 hours of operation), the capacity retention rate reached 100% (specific capacity remained at 163 mAh / g), and the coulombic efficiency remained stable at around 100%; while the blank control sample failed within approximately 100 cycles. The cycle life improvement effect of this invention has achieved unexpected and significant progress. Attached Figure Description

[0031] Figure 1 This is a comparison chart of the long cycle life of Zn||VO2 full cells using the electrolyte of this invention and the comparative electrolyte at low current densities.

[0032] Figure 2 This is a three-dimensional profile of the electrode interface after the electrolyte of this invention has been circulated, obtained by time-of-flight secondary ion mass spectrometry. Detailed Implementation

[0033] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0034] Unless otherwise specified, the raw materials and reagents used in the embodiments of this application were all purchased commercially.

[0035] Among them, n-dodecyl phosphate choline (DPC, CAS No.: 29557-51-5) can be purchased from companies such as Aladdin and Bid.

[0036] Example 1 Dissolve 2 mol / L zinc sulfate (ZnSO4) in deionized water and stir magnetically at room temperature until completely dissolved; then add n-dodecyl phosphate choline (DPC) to the above solution to make its concentration 0.05 mol / L, and continue stirring at room temperature for 30 min until completely dissolved to obtain the aqueous zinc-ion battery electrolyte of the present invention (denoted as DPC-0.05).

[0037] The above electrolyte was used to assemble a zinc symmetric battery (Zn||Zn): 99.9% pure zinc foil was used as the positive and negative electrodes, respectively, and a glass fiber membrane was used as the separator. The electrolyte was injected to assemble a coin cell. At 10 mA / cm² 2 The current density was used to perform constant current charge and discharge tests, with each charge and discharge cycle lasting 1 hour.

[0038] The results show that the cycle life and coulombic efficiency (CE) of the zinc symmetric battery using the electrolyte of the present invention (DPC-0.05) are significantly better than those of the control group (Comparative Example 1) using only 2 mol / L ZnSO4 blank electrolyte, and the voltage polarization remains stable during long-term cycling.

[0039] Example 2 The difference from Example 1 is that the concentration of n-dodecylphosphocholine (DPC) was 0.1 mol / L (denoted as DPC-0.1). The remaining steps were the same as in Example 1. The results showed that the zinc-symmetric battery cycling performance of the DPC-0.1 electrolyte was superior to that of Comparative Example 1.

[0040] Example 3 The difference from Example 1 is that the concentration of n-dodecylphosphocholine (DPC) was 0.2 mol / L (denoted as DPC-0.2). The remaining steps were the same as in Example 1. The results showed that the zinc-symmetric battery cycling performance of the DPC-0.2 electrolyte was superior to that of Comparative Example 1.

[0041] Example 4 The difference from Example 1 is that zinc sulfate (ZnSO4) was replaced with zinc trifluoromethanesulfonate (Zn(CF3SO3)2), while the rest of the preparation method remained the same, resulting in an aqueous zinc-ion battery electrolyte. This electrolyte was used to assemble a battery, and the test results showed that after 1000 cycles at a current density of 1 A / g, the capacity retention was 92.3%, and the coulombic efficiency was 99.7%.

[0042] Example 5 Full cell assembly: Using the electrolyte (DPC-0.1) prepared in Example 2 as the electrolyte, vanadium dioxide (VO2) as the positive electrode active material, 99.9% pure zinc foil as the negative electrode, and a glass fiber membrane as the separator, a full cell was assembled. Charge-discharge tests were conducted at a current density of 0.2 A / g, with a test voltage range of 0.2~1.6 V (vs. Zn). 2+ / Zn).

[0043] The results show that the Zn||VO2 full cell using the electrolyte of this invention (DPC-0.1) at a current density of 0.2 A / g, after 3600 charge-discharge cycles (a total of 7000 hours), has an initial specific capacity of 163 mAh / g and a final specific capacity of 163 mAh / g, achieving 100% capacity retention. The coulombic efficiency remains stably around 100% throughout the entire cycle (e.g., ...). Figure 1 (As shown). Comparative Example 1 (blank electrolyte) rapidly decayed to failure in specific capacity and coulombic efficiency within about 100 cycles, and its cycle life was much shorter than that of the electrolyte of the present invention.

[0044] Comparative Example 1 Blank electrolyte: Only a 2 mol / L deionized ZnSO4 aqueous solution was used as the electrolyte, without any additives. The remaining battery assembly and testing procedures were the same as in Example 1. The results showed that the zinc symmetric battery of Comparative Example 1 experienced a significant increase in voltage polarization and even a short circuit after a short cycle time, and its cycle life was much shorter than that of Examples 1-3.

[0045] Comparative Example 2 The difference from Example 1 is that the amphiphilic zwitterionic additive, n-dodecyl phosphate choline (DPC), is replaced with n-ethyl phosphate choline (EPC, CAS No.: 107-45-9), with a concentration of 0.1 mol / L. The remaining steps are the same as in Example 1.

[0046] The above electrolyte was used to assemble a zinc symmetric battery (Zn||Zn): 99.9% pure zinc foil was used as the positive and negative electrodes, respectively, and a glass fiber membrane was used as the separator. The electrolyte was injected to assemble a coin cell. At 10 mA / cm² 2 The current density was used to perform constant current charge and discharge tests, with each charge and discharge cycle lasting 1 hour.

[0047] The results show that the cycle life of the zinc symmetric battery using the electrolyte of Comparative Example 2 (EPC-0.1) is significantly lower than that of Example 1 (DPC-0.1). After about 500 cycles, the voltage polarization of Comparative Example 2 begins to increase significantly, and after 1000 cycles, the capacity retention is only about 65% of that of Example 1, and the coulombic efficiency also shows a significant decline.

[0048] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An aqueous zinc-ion battery electrolyte, characterized in that, The aqueous zinc-ion battery electrolyte comprises an amphiphilic zwitterionic additive, a zinc salt, and water; The amphiphilic zwitterionic additive includes hydrophobic groups and hydrophilic zwitterionic head groups; The hydrophobic group is selected from long-chain alkyl groups; The long-chain alkyl group is a dodecyl group; The hydrophilic zwitterionic head group is selected from the phosphoric acid choline group.

2. The aqueous zinc-ion battery electrolyte according to claim 1, characterized in that, The zinc salt is selected from at least one of zinc sulfate and zinc trifluoromethanesulfonate.

3. The aqueous zinc-ion battery electrolyte according to claim 1, characterized in that, The amphiphilic zwitterionic additive is selected from n-dodecyl phosphate choline.

4. The aqueous zinc-ion battery electrolyte according to claim 1, characterized in that, The concentration of the amphiphilic zwitterionic additive is 0.005 mol / L to 1 mol / L; Preferably, the concentration of the amphiphilic zwitterionic additive is 0.01 mol / L to 0.5 mol / L; More preferably, the concentration of the amphiphilic zwitterionic additive is 0.05 mol / L to 0.2 mol / L.

5. The aqueous zinc-ion battery electrolyte according to claim 1, characterized in that, The concentration of the zinc salt is 0.5 mol / L to 4 mol / L; Preferably, the concentration of the zinc salt is 1 mol / L to 3 mol / L.

6. The aqueous zinc-ion battery electrolyte according to claim 1, characterized in that, The water is deionized water.

7. A method for preparing an aqueous zinc-ion battery electrolyte as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Zinc salt is added to water and stirred to dissolve. Then, an amphiphilic zwitterionic additive is added and stirred until completely dissolved to obtain the aqueous zinc-ion battery electrolyte. Preferably, the stirring time is 10 min to 60 min.

8. An aqueous zinc-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an aqueous zinc-ion battery electrolyte as described in any one of claims 1 to 6.

9. The aqueous zinc-ion battery according to claim 8, characterized in that, The negative electrode is metallic zinc or a zinc alloy; Preferably, the negative electrode is a zinc sheet or zinc foil with a purity of not less than 99.9%.

10. The aqueous zinc-ion battery according to claim 8, characterized in that, The active material of the positive electrode is selected from ammonium vanadate, vanadium pentoxide, or vanadium dioxide.